Accumulation of proanthocyanidin monomers in two genotypes of blood-flesh peach. Issue 5 (3rd September 2017) - Yan, Juan; Cai, Zhixiang; Shen, Zhijun; Ma, Ruijuan; Yu, Mingliang
ABSTRACT: Accumulation of proanthocyanidin monomers (catechin and epicatechin) was revealed in flesh tissues during fruit development in two blood-flesh peach ( Prunus persica (L.) Batsch) genotypes, 'Beijingyixianhong' ( DBF- genotype) and 'Heiyoutao' ( bfbf- genotype). The activities of two key enzymes, leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR), were measured, and their activities and coding genes' expression profiles were compared at the transcription level over the fruit development period. There were different developmental profiles of catechin and epicatechin concentrations between the genotypes. In 'Beijingyixianhong', catechin and epicatechin concentrations remained low early in fruit development, increased gradually at the ripening stages, and reached maxima at the mature stage. In 'Heiyoutao', catechin and epicatechin concentrations were very low at the early stage of fruit development, with rapid accumulation to maxima at the middle development stage; however, they decreased during ripening. Activities of LAR and ANR, as well as the relative expression of their coding genes at the transcriptional level, were consistent with accumulation of proanthocyanidin monomers in each blood-flesh peach genotype. ANR activity and the quantitative expression of its coding gene were much more closely related to proanthocyanidin accumulation than was the case for LAR, which caused higher and more dramatic changes in epicatechin concentrations during fruit development in both genotypes of blood-flesh peach.